THE IMPACT OF MENTAL FITNESS ACTIVITIES ON THE PHYSICAL CONDITION OF MATURE WOMEN (Physical Culture and Sport: Scientific Perspective, 2025)
The purpose of this study was to assess the impact of mind-body fitness practices, particularly Hatha yoga, on the physical condition of young women aged 32 to 45. In modern society, young women often experience physiological changes, emotional stress, and low levels of physical activity. Therefore, holistic approaches to wellness that integrate both physical training and psycho-emotional regulation, such as Hatha yoga, are becoming increasingly relevant. Materials and Methods. The study included 33 young women aged 32 to 45 who regularly attended yoga classes for at least one year, and 13 fitness trainers. The methodology involved theoretical analysis, sociological surveys, anthropometric and functional testing, pedagogical observation, and statistical evaluation. The study was conducted in fitness clubs in Ivano-Frankivsk, Ukraine. Baseline testing measured flexibility, muscular endurance, balance, body composition, and respiratory function. After a 3-month Hatha yoga training program, all measurements were repeated. Results. The findings revealed significant positive changes across all measured parameters. Core muscular endurance (plank test) improved by 76.5%, spinal flexibility by 58.7%, and balance (Flamingo test) by 42%. Respiratory function also improved, with the Stange test increasing by 26.95% and the Genchi test by 29.32%. Participants' body composition shifted toward healthier fat-to-muscle ratios, and BMI remained within the normal range. Conclusions. Hatha yoga proved to be an effective method for enhancing the physical condition of young women, particularly in improving strength, flexibility, coordination, and functional fitness. The comprehensive nature of Hatha yoga—which includes physical postures (asanas), breathing exercises (pranayama), relaxation, and meditative components—makes it a valuable addition to fitness programs targeting this demographic. These results support further research into long-term effects and broader implementation of such practices.
Keywords: mind-body fitness; Hatha yoga; physical condition; young women; flexibility; breathing exercises